An augmented delivery of the anticancer agent, curcumin, to the colon - Sabra, Rayan; Billa, Nashiru; Roberts, Clive J. (Elsevier, 2018)
This work describes the formulation aspects of an orally viable curcumin-containing mucoadhesive nanoparticulate system for management of colon cancer. Curcumin is documented to possess anticancer properties whilst modified citrus pectin yields a galactose functionality capable of inhibiting the growth and proliferation of colon cancer cells due to antagonism to galectin-3 (Gal-3). A successfully formulated curcumin containing chitosan-modified citrus pectinate nanoparticles (MCPCNPs) registered a z-average of 178 nm (± 0.896) and a positive surface charge of + 35.7 mV (± 1.41). The MCPCNPs presented high mucoadhesion propensity in the colonic region/ media and minimal at pH 1.2 (stomach). There was approximately 18 % curcumin release at pH 1.2 over 2 h and up to 68% release in the 33% (w/v) caecal medium over 24 h. The data obtained strongly suggests that the formulated MCPCNPs have the potential to be applied as an orally deliverable colon cancer formulation alternative in the treatment of colon cancer.